Peramalan Jumlah Wisatawan Mancanegara yang Datang ke Bali Tahun 2025 Menggunakan SARIMAX dan Data Google Trends - Ayuningrum, Adinda Safira Santoso; Sari, Nindy Candra Ayu Puspa; Ihsan, Nur Faqih; -, Nasrudin (Seminar Nasional Official Statistics, 2025)
Bali is a tourist destination that is in demand by foreign tourists, which continues to increase every year, so the government and local communities need strategies or policies that can be taken so that this becomes an advantage. There is a gap in the data available by the Central Statistics Agency (BPS) as the data provider, so Google Trends is used to fill the gap. Tourist projections rely heavily on historical data sourced from conventional statistical reports, which, although they have a high level of accuracy, are often accompanied by significant time lags and are less responsive to dynamic changes in tourist behavior. This research aims to provide more accurate and responsive predictions by considering exogenous variables in the form of GTI with the keywords "Bali", "Bali Hotel", "Bali `Flight", and "Bali Destination". The best model selected was SARIMAX(2,0,0)(2,1,0)12, with RMSE and sMAPE of 5.994 and 0.845. The number of foreign tourists coming to Bali is estimated to reach its peak in August 2025 at 641,553 people.